Tortilla Cheese / Mohamad Alieff Haikal Ismail and Mohammad Airul Mohd Fauzi - Ismail, Mohamad Alieff Haikal; Mohd Fauzi, Mohammad Airul (2022)
Tortilla Cheese is categorized as a snack.We are interested in choosing to sell such food as our business is because we believe this food can soar on social media and in the market because Tortilla Cheese is very popular with many people regardless of age, especially those who love chocolate. This is because, the main ingredient used by this food is chocolate. Tortilla Cheese is a snack sale that can be said to be in high demand and popular and the ingredients used are also quality. I as a trader believe that food quality is very important in business. We also want these Tortilla Cheese customers to always be satisfied with their food. We also hope the sale of Tortilla Cheese will continue to grow and become famous in the future. Tortilla Cheese is very special because it is made by homemade and uses only quality ingredients. The most famous main ingredient in Tortilla Cheese is that we use original Tortilla Cheese Brands. This cheese is not too sweet and suitable for all ages and guarantees the satisfaction of our customers.The packaging for Tortilla Cheese is also well handled by us so that no damage can affect the Tortilla Cheese business.